Beyond Borders: Assessing the Influence of Geopolitical Tensions on Sovereign Risk Dynamics - António Afonso; José Alves; Sofia Monteiro (Center for Economic Studies and ifo Institute (CESifo), 2023)
We assess the impact of geopolitical risk and world uncertainty on the sovereign debt risk of 26 European Economies during the period 1984-2022, through the implementation of OLS-Fixed Effects regressions and the Generalized Method of Moments (GMM). We find that geopolitical tensions and global uncertainty in border countries contribute to the rise of European country's sovereign risk as measured by 5- and 10-year Credit Default Swaps (CDS) and bond returns. Moreover, this interconnection is more pronounced during turbulent times such as the subprime crisis. Lastly, we found that geopolitical tensions in other country' groups such as South America and Asia have a significant impact on the government risks of European countries.
Keywords: C23; E44; G32; H63; 330; geopolitical risk; world uncertainty; political tensions; sovereign risk; European economy; GMM; subprime crisis